ADMINISTRATIVE COURTS A DEFENSE AGAINST POPULISM - DOI 10.5935/2448-0517.20200034 - Fierro, Ana (Juris Poiesis - Qualis A3, 2020)
Over the past two decades, populist governments have proliferated in America. These governments are characterized by reducing to mere formalism the procedures of control of the rule and intervene in the judiciary and administrative courts. Modern society worked hard to achieve legal systems based on the rule of law, in order to prevent citizens from being subject to the will of one leader. In our legal systems administrative courts play a fundamental role improving state bodies. This paper explores the use of administrative courts as accountability mechanisms that protect the rule of law. We suggest that administrative courts are powerful procedures for accountability and control against abuse of powers. Finally, we recommend states should broaden access to these mechanisms, given the fact that administrative trails are still very restricted to most of the citizens."